2020
DOI: 10.26650/iuitfd.2020.0024
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis, Management and Clinicopathological Features of Acute Appendicitis in Pregnant Women and Its Impact on Fetal Outcomes

Abstract: Çalışmanın amacı gebe kadınlarda görülen apandisitin tanı ve tedavi stratejileri ile klinikopatolojik özellikleri ve feto-maternal sonuçlarını değerlendirmektir. Gereç ve Yöntem: Bu çalışmada apendektomi yapılan 17 gebe kadın ve yaşları eşleştirilmiş 59 gebe olmayan kadın laboratuvar bulguları, preoperatif ultrasonografi (USG), patoloji ve klinik sonuçlar açısından karşılaştırıldı. Bulgular: Toplam USG tarama sayısı, görüntülenemeyen apandis oranları ve hastanede kalış süreleri gebe kadınlarda gebe olmayan kad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 26 publications
1
3
1
Order By: Relevance
“…Although laparoscopic surgery was performed in approximately 38% of women diagnosed with acute appendicitis between the study dates, especially in recent years, it was observed that open appendectomy was performed in all pregnant patients. Examining the literature, it was seen that similar results are given in small centers, in accordance with the data in the present study (9,18,19). Laparoscopic surgery is more commonly used in larger centers.…”
Section: Graphic 1bsupporting
confidence: 92%
See 1 more Smart Citation
“…Although laparoscopic surgery was performed in approximately 38% of women diagnosed with acute appendicitis between the study dates, especially in recent years, it was observed that open appendectomy was performed in all pregnant patients. Examining the literature, it was seen that similar results are given in small centers, in accordance with the data in the present study (9,18,19). Laparoscopic surgery is more commonly used in larger centers.…”
Section: Graphic 1bsupporting
confidence: 92%
“…In the present study, it was seen that spinal anesthesia was preferred in 6.1% of nonpregnant patients, while 77.8% of pregnant patients. These rates were higher than those reported in the literature (9,18,19). This may be due to the defensive approach of anesthesiologists and surgeons.…”
Section: Graphic 1bcontrasting
confidence: 63%
“…According to previous studies, the WBC value was significantly higher in patients who underwent AA operation compared with healthy pregnant women and pregnant women with a prediagnosis of AA 4,9 . Moreover, WBC level was found to be higher in pregnant patients with AA diagnosis than in non‐pregnant women with AA diagnosis 16,17 . Previous studies have reported that WBC in AA diagnosis has a sensitivity range of 57.1–72.5%, a specificity range of 52.0–82.9%, and an AUC value of 0.661 4,18 .…”
Section: Discussionmentioning
confidence: 92%
“…4,9 Moreover, WBC level was found to be higher in pregnant patients with AA diagnosis than in non-pregnant women with AA diagnosis. 16,17 Previous studies have reported that WBC in AA diagnosis has a sensitivity range of 57.1-72.5%, a specificity range of 52.0-82.9%, and an AUC value of 0.661. 4,18 WBC value is significantly higher in complicated appendicitis than in uncomplicated appendicitis.…”
Section: Discussionmentioning
confidence: 99%
“…Research on the best surgical technique for treating acute appendicitis among pregnant women has shown inconsistent findings. (ŞENOCAK et al, 2020). This study intends to give knowledge about the best surgical technique for treating acute appendicitis among pregnant women.…”
Section: Introductionmentioning
confidence: 99%